Pengaruh Budaya Organisasi, Disiplin Kerja Dan Motivasi Terhadap Loyalitas Guru dan Pegawai Di SD Swasta Al-Azhar 1 Medan - Dewi, Sri Puspa; Surbakti, Syamsul Bahri; Pasaribu, Aria Masdiana; Sari, Putri Krisna (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2023)
This examination breaks down the impacts of Authoritative Culture, Work Discipline and Accomplishment Inspiration on the Dependability of Educators and Representatives in Confidential Grade Schools at Al-Azhar 1 Medan Private Primary School. The population in this proposition is all educators and workers at the Al-Azhar 1 Medan Private Elementary School, adding up to 37 individuals. The example for this examination is 37 respondents using a testing procedure using an immersed inspection method. The technique utilized is different straight relapse (multilinear relapse examination) using a quantitative story approach. The exploration results show that some of the factors Hierarchical Culture, Work Discipline and Accomplishment Inspiration affect Educator and Representative Unwaveringness. At the same time, the general factors of Hierarchical Culture, Work Discipline and Accomplishment Inspiration meaningfully affect Instructor and Representative Faithfulness.